Upaya Meningkatkan Kreativitas Belajar Biologi Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe Number Head Together (NHT) Di MAN Siabu - Arni Maya; Nurmaini Ginting; Sahlan Tuah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2019)
The problem faced is the lack of student interest; this is because biology subjects make students easily bored and assume biology is one of the difficult subjects. At the time of observation the teacher is more dominant in the learning process, so students' creativity is lacking. Learning models are needed that are appropriate learning models so as to be able to increase student creativity in sparking ideas, answers, solving problems or questions, skills in seeing problems from different points of view, the ability to give birth to new and unique expressions and able to improve students' abilities in terms of skills or develop students' ideas in the learning process. This type of research is classroom action research with a Number Head Together (NHT) type of cooperative learning model. The results of the first cycle students' creativity test results 78.94% while in the second cycle increased 5.27% with a percentage of 84.21%, the results of observations on students in the first cycle showed the results of 65.27% experienced an increase of 10.45% in the cycle II with the results of a percentage of 75.72% and the results of observations of the activities of teachers in the first cycle obtained 72% in the second cycle increased by 16% to 88%. From this study it was concluded that through the Number Head Together (NHT) learning model can increase creativity Grade XI student MIA 2 MAN Siabu.Keywords: Creativity, Number Head Together, Classroom Action Research